Threats to the arctic - Elias, Scott A. (Elsevier, 2021)
Threats to the Arctic discusses all the current threats to this fragile region, emphasizing the interconnections between many environmental impacts, as well as the teleconnections between events already emerging in the Arctic (ocean circulation changes, melting of sea ice, glaciers and ice sheets) and other parts of the world. The book's aim is to inform readers about the impending, sometimes irreversible changes coming to the Arctic. University students, environmental engineers, policymakers and sociologists with an interest in the role of the Arctic in global change will benefit from the book's unique perspective. As this remote, inhospitable part of the world that few people will ever visit provides amazing insights, we can no longer have an 'out of sight - out of mind' approach to the environmental upheavals taking place in the Arctic.